2023
DOI: 10.1111/jebm.12548
|View full text |Cite
|
Sign up to set email alerts
|

Exploring patient medication adherence and data mining methods in clinical big data: A contemporary review

Yixian Xu,
Xinkai Zheng,
Yuanjie Li
et al.

Abstract: BackgroundIncreasingly, patient medication adherence data are being consolidated from claims databases and electronic health records (EHRs). Such databases offer an indirect avenue to gauge medication adherence in our data‐rich healthcare milieu. The surge in data accessibility, coupled with the pressing need for its conversion to actionable insights, has spotlighted data mining, with machine learning (ML) emerging as a pivotal technique. Nonadherence poses heightened health risks and escalates medical costs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 333 publications
0
6
0
Order By: Relevance
“…In addition to determining the optimal treatment plan, strict drug adherence is important in IBD because of its recurrence. 203 An increasing number of treatments are expected to emerge in the future in the field of IBD; however, early detection, diagnosis, and treatment are more important (Figure 3).…”
Section: Treatment Of Complicationsmentioning
confidence: 99%
“…In addition to determining the optimal treatment plan, strict drug adherence is important in IBD because of its recurrence. 203 An increasing number of treatments are expected to emerge in the future in the field of IBD; however, early detection, diagnosis, and treatment are more important (Figure 3).…”
Section: Treatment Of Complicationsmentioning
confidence: 99%
“…The study used structured query language (SQL) to extract the data 20 . The following data were extracted:…”
Section: Introductionmentioning
confidence: 99%
“…The MIMIC-IV combines electronic medical records from different sources, providing researchers with a vast amount of data that includes patient demographics, vital statistics, laboratory results, and diagnoses. The diagnoses were made using the International Classi cation of Diseases, Ninth Revision (ICD-9) and Tenth Revision (ICD-10) codes 20,21 . As the data in this database were deidenti ed, informed consent from patients was not required for this study.…”
mentioning
confidence: 99%
“…Other inputs include cardiovascular health, drug and smoking use, stress level, and demographic factors. In total, LIBRA's 42 entries provide a multidimensional profile of lifestyle factors affecting brain health [28].…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have evaluated the diagnostic utility of BALI, LIBRA, and DTI separately [28]. For example, several studies using BALI-derived volumetrics such as hippocampal atrophy have demonstrated accuracy in distinguishing Alzheimer's patients from controls [29].…”
Section: Introductionmentioning
confidence: 99%